Fostering political participation among students of Pesantren through new media in Madura - Cholil, Ahmad; Zanuddin, Hasmah (International Journal of Engineering and Technology, 2018)
There are 911 of Islamic boarding schools in Madura. However, the students do not have easy access to the media via the Internet as expected. This is particularly due to some restrictions imposed by the schools on them in accessing the Internet. This resulted in the study of communication action between students of Islamic boarding schools and the new internet media; that is, how the schools and students can absorb the use of new media among students and how they play roles in political participation through new internet media. The present study employs a qualitative approach using ethnographic observations. The study uses Rogers’ (1986) theory on the diffusion of innovation organizations and individuals, Roth’s (1980) theory on political participation, and Wilson’s (1980) theory on the pyramid of political participation. Based on diffusion of organizational innovation, it was found that the Banyuanyar Islamic boarding schools accept the existence of the Internet, but they experience lack of computer equipment (hardware), application program (software), as well as lack of experts and skills to use the facilities. As for the communication action, the use of the Internet gains wide acceptance. Most of the students even have basic knowledge to use the Internet before they enter school. The existence of media facilities may lead to the breach of rules by the students with regard to the policies of pesantren. Some efforts are needed to identify ethical violations in communication actions undertaken by the students in the use of the Internet. On the one hand, the identification of the Internet provides freedom space, but on the other, the pesantren does not have virtual security officers to deal with digital violations that may be committed by the students. The early identification of an effort is necessary to anticipate the adoption of innovations and to make boarding school students media-intelligent. In term of the tendency of political participation, the students of pesantren Banyuanyar are participative in political activities. The policy made by the pesantren leaders plays a pivotal role in political participation. The education on political participation among students of pesantren through new media is reflected in the flow of information that is accessible everywhere, particularly electronic media, which has contributed significantly to developing the mindset of the people, especially among the students of pesantren.